(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction: Penetrating aortic ulcer (PAU) is a severe pathological entity within the spectrum of acute aortic syndromes, most commonly occurring in elderly patients with advanced atherosclerosis. Although PAU may remain clinically silent, it carries a substantial risk of aortic rupture with a high mortality rate. Case presentation: We report the case of a 73-year-old male with a history of coronary artery disease treated with coronary stenting and longstanding hypertension. The patient was admitted for severe right arm pain and was subsequently diagnosed with plasmacytoma following biopsy. During contrast-enhanced computed tomography performed for evaluation of bone tumor involvement and coronary stent status, an incidental penetrating aortic ulcer was identified at the level of the aortic arch, with deep extension through the intimal layer. Given the imminent risk of life-threatening aortic rupture, a multidisciplinary team decided to prioritize cardiovascular management using a hybrid surgical strategy. The procedure consisted of carotid–carotid artery bypass combined with endovascular stent-graft deployment to cover the lesion in a single operative session. Conclusion: The procedure was successful, and the patient recovered uneventfully, being discharged after two weeks to continue oncologic treatment. This case highlights the critical importance of incidental detection of cardiovascular lesions through imaging studies in oncologic patients and underscores the safety and efficacy of hybrid surgery for managing complex aortic arch lesions in elderly patients with multiple comorbidities.